The Modes of Entry of DM-Drogerie Markt into the Turkish Market - Abbasov, Rahman (2023)
In my thesis, main idea is choosing appropriate mode of entry into Turkish market for the name of DM Drogerie markt. In order to interpret the best conclusion, I used factors, selection process, some strategies, modes of entries, about DM and its market position, PEST, SWOT and some more methots.